Role of catecholamines in acute hypertensive response: subarachnoid hemorrhage versus spontaneous intracerebral hemorrhage. Issue 3 (June 2015) - Inamasu, Joji; Moriya, Shigeta; Oheda, Motoki; Hasegawa, Mitsuhiro; Hirose, Yuichi
Abstract : Background and objective: Acute hypertensive response, defined as systolic blood pressure (SBP) 140 mmHg or more within 24 h of onset, is frequently observed in hemorrhagic stroke patients. Although catecholamine surge is pivotal in its pathogenesis, few studies have evaluated the relationship between admission SBP and plasma catecholamine levels. Patients and methods: A prospective observational study was carried out to investigate potential differences in the acute hypertensive reaction between subarachnoid hemorrhage (SAH) and spontaneous intracerebral hemorrhage (SICH) by analyzing 200 SAH and 200 SICH patients. In each category, patients were quadrichotomized on the basis of their SBPs in emergency department: less than 140 mmHg, 140–184 mmHg, 185–219 mmHg, and 220 mmHg or more. The plasma catecholamine levels were compared among the four groups. Furthermore, multivariate regression analyses were carried out to identify variables correlated with hypertensive emergency (SBP≥185 mmHg). Results: In SAH patients, there was a proportional increase in norepinephrine levels relative to the graded SBPs, and norepinephrine levels in the 220 mmHg or more group were significantly higher than those in the less than 140 mmHg group (1596±264 vs. 853±124 pg/ml, P =0.03). By contrast, no proportional increase in norepinephrine levels to the graded SBPs was observed in SICH patients. Multivariate regression analyses showed that the initial Glasgow Coma Scale scores of 8 or less (odds ratio 2.251, 95% confidence interval 1.002–5.117) and plasma norepinephrine levels (odds ratio 1.002, 95% confidence interval 1.001–1.003) were correlated with hypertensive emergency in SAH patients. By contrast, none of the variables evaluated were correlated with hypertensive emergency in SICH patients. Conclusion: An acute hypertensive response may be more complex, multifactorial, and less catecholamine dependent in SICH patients compared with SAH patients.